Mixed Marriages without Prenuptial Agreements in Indonesia: Legal Uncertainty and the Quest for Reform - Prinz, Sulami (Jurnal Bedah Hukum, 2025)
Abstract  A significant concern in mixed marriages is the absence of a prenuptial agreement, which can result in legal complications, particularly concerning property ownership and citizenship rights. In the absence of an agreement, joint property acquired during the marriage may be subject to restrictions, particularly with regard to the ownership of immovable assets by the foreign spouse. The situation is further complicated by the differences in legal systems between the countries of each spouse, which may lead to legal conflicts. The methodological approach employed is underpinned by normative research, bolstered by statutory frameworks, legal concepts, and legal facts. The present study examines the legal position of mixed marriages conducted without a prenuptial agreement, with a focus on its implications for joint property ownership, inheritance rights, and legal certainty. The research findings indicate that the absence of a prenuptial agreement has the potential to impose limitations on the property rights of spouses and engender legal ambiguity. This underscores the necessity for a more explicit legal framework and heightened public awareness regarding the significance of prenuptial agreements. Abstrak Masalah utama dalam pernikahan campuran adalah tidak adanya perjanjian pranikah, yang dapat menyebabkan berbagai komplikasi hukum, terutama dalam hal kepemilikan properti dan hak kewarganegaraan. Tanpa perjanjian, harta bersama yang diperoleh selama pernikahan mungkin tunduk pada batasan, terutama mengenai kepemilikan aset tidak bergerak oleh pasangan asing. Situasi ini semakin diperumit oleh perbedaan sistem hukum antara negara masing-masing pasangan, yang dapat menyebabkan konflik hukum. Metode yang digunakan adalah penelitian normatif yang didukung oleh pendekatan perundang-undangan, konsep hukum, dan fakta hukum. Penelitian ini mengkaji kedudukan hukum perkawinan campuran yang dilakukan tanpa perjanjian pranikah, dengan fokus pada implikasinya terhadap kepemilikan harta bersama, hak waris, dan kepastian hukum. Temuan-temuan penelitian mengungkapkan bahwa ketiadaan perjanjian pranikah dapat membatasi hak-hak kepemilikan pasangan dan menciptakan ambiguitas hukum, sehingga menekankan perlunya kerangka hukum yang jelas dan kesadaran masyarakat akan pentingnya perjanjian pranikah.-Kesimpulannya bahwa ketiadaan pengaturan yang eksplisit sebelum pernikahan dapat membatasi ruang perlindungan hukum terhadap hak kepemilikan individual dalam pernikahan.